A Model for Measuring the Academic Achievement of Student-Athletes - Whitner, Phillip A. (My University, 1990)
Colleges and universities that actively recruit and accept young men and women as athletes have responsibilities to these young people. One responsibility is to provide these young people with comparable academic achievement data regarding both the student-athlete and the general student population. To assist in meeting the challenge of this responsibility a method, or model, for measuring academic achievement is proposed for national acceptance.
Keywords: models; legislation; academic performance; academic predictors